2019
DOI: 10.1039/c9ee01334b
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and elucidating the effect of CO2 on the thermodynamics, kinetics and charge transport of AEMFCs

Abstract: Exposing operating AEMFCs to CO2 leads to performance-robbing overpotentials, linked to fundamental thermodynamics, transport and kinetics – the impact of which can be reduced through careful systems design and selection of operating conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
118
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(122 citation statements)
references
References 34 publications
(57 reference statements)
2
118
0
2
Order By: Relevance
“…This third effect was captured quite well in the Gerhardt model [23]. Therefore, the operating voltage for an AEMFC with CO 2 in the cathode feed can be described by Equation (3) 16 :…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…This third effect was captured quite well in the Gerhardt model [23]. Therefore, the operating voltage for an AEMFC with CO 2 in the cathode feed can be described by Equation (3) 16 :…”
Section: Introductionmentioning
confidence: 81%
“…Now that AEMFC performance and stability have been enhanced to the point where their future deployment in real applications is realistic, it is an important time in AEMFC development to begin to answer some of the contemporary issues that have to date been mostly put aside in the literature, including operating on real air, which contains CO 2 , leading to the carbonation discussed above. Recently, there have been several experimental [16][17][18][19][20][21] and modeling [22][23][24][25] studies that have allowed researchers in the field to well-understand how adding CO 2 to high performing AEMFCs influences their behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, due to the very different operational conditions, new challenges are also faced, among which the presence of CO 2 is the most important one. [25][26][27] By analyzing the anode gas composition during CO 2 reduction, HCO 3 À and CO 3 2À were identified as majority charge carriers responsible for the ion conduction through the AEM (and not OH À such as in water electrolysis), due to the rapid formation of HCO 3 À and CO 3…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress has been achieved recently in the field of anion exchange membrane fuel cells (AEMFCs). [1][2][3] In spite of the remarkable development of this technology, the deployment of AEMFCs is still hindered by the chemical degradation of the anion exchange membrane (AEM) and ionomers, [4][5][6][7][8][9][10][11] carbonation issues, [12][13][14][15] and by the sluggish kinetics of the hydrogen oxidation reaction (HOR). [2,16,17] It has been shown that the HOR kinetics in alkaline media is two to three orders of magnitude lower than that in acidic media, [18,19] even for the most active catalysts such as Pt, [17,[19][20][21][22] Rh, [23] and Ir.…”
Section: Introductionmentioning
confidence: 99%